Assessment of Impact of Creativity Teaching Program on Teachers’ Knowledge, Attitude, and Skill - Afzal-os-sadat Hossieni (فصلنامه نوآوری‌های آموزشی, 2003)
Creativity is a Devine gift and each individual has a certain amount of this gift. The realization and appearance of creativity requires a proper location. The expansion of this ability, which can be said is the survival of a society, is possible through educational programming, and accurate and proper teaching and education. Teachers, as one of the most important training and education elements, have a key role in nourishing creativity. The teachers’ attitude toward creativity, their level of understanding of it, and also their type of attitude and teaching method have a direct relationship on enriching the class environment for students’ growth of creativity. Therefore it is necessary to help the teachers gain the attitude and necessary skills for the growth of the students’ creative ability. In order to assess how creativity is taught in elementary school period, 120 instructors were participating (60 instructors in a test group and 60 instructors in a control group). The test group became involved in “Teaching of creativity” program so that the impact of the program and training model on instructors’ knowledge, attitude, and skill would be assessed. The results were examined through T test and showed that there is significant difference between the two groups – The “test group” and the “control group”. The results stated the positive impact of the training period. A set of suggestions have been made for the growth of students’ creativity based on the findings in this research.